A Study on the establishment of autonomous operation system for data-based water purification facilities - Park, Daewon (KDI School, 2021)
This research paper aims to lay the foundation for the establishment of a data-driven water purification plant autonomous operation system by presenting how to generate and transmit the underlying measurements of the data and manage the acquired data. It also identified the role required for operators who work 24 hours a day at the water purification plant to settle down stably when introducing an autonomous operation system for water purification plants. For this study, papers and data related to automatic operation of water purification plant s and smart factories were collected and analyzed, and in-depth interviews with K-water''s related business experts were conducted to identify problems and needs. Based on this, the directi on that should be preceded to establish an autonomous operation system in the water purification plant was presented. Finally, I think this study is meaningful in laying the foundation stone so that it can be studied and developed in a more improved way rather than a methodology that enables the establishment of a water purification plant autonomous operation system.
Thesis(Master) --KDI School:Master of Public Management,2021.